Demographic and clinical profile of black patients with chronic kidney disease attending a tertiary hospital in Johannesburg, South Africa - Meremo, Alfred; Paget, Graham; Duarte, Raquel; Dickens, Caroline; Dix-Peek, Therese; Bintabara, Deogratius; Naicker, Saraladevi (PloS one, 2022)
The prevalence of chronic kidney disease (CKD) is increasing worldwide; black patients have an increased risk of developing CKD and end stage kidney disease (ESKD) at significantly higher rates than other races. A cross sectional study was carried out on black patients with CKD attending the kidney outpatient clinic at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) in South Africa, between September 2019 to March 2020. Demographic and clinical data were extracted from the ongoing kidney outpatient clinic records and interviews, and were filled in a questionnaire. Patients provided blood and urine for laboratory investigations as standard of care, and data were descriptively and inferentially entered into REDcap and analysed using STATA version 17. Multivariable logistic regression analysis was used to identify demographic and clinical variables associated with advanced CKD. A total of 312 black patients with CKD were enrolled in the study with a median age of 58 (IQR 46-67) years; 58% patients had advanced CKD, 31.5% of whom had grossly increased proteinuria, 96.7% had hypertension, 38.7% had diabetes mellitus and 38.1% had both hypertension and diabetes mellitus. In patients with advanced CKD, the median age was 61 (IQR 51-69) years, eGFR 33 (30-39) mL/min/1.73 m.sup.2, serum bicarbonate 22 (IQR 20-24), haemoglobin 12.9 (IQR 11.5-14.0) g/dl and serum uric acid 0.43 (IQR 0.37-0.53). The prevalence of metabolic acidosis was 62.4%, anemia 46.4% and gout 30.9% among those with advanced CKD, while the prevalence of metabolic acidosis and anaemia was 46.6% and 25.9% respectively in those with early CKD. Variables with higher odds for advanced CKD after multivariable logistic regression analysis were hypertension (OR 3.3, 95% CI 1.2-9.2, P = 0.020), diabetes mellitus (OR 1.8, 95% CI 1.1-3.3, P = 0.024), severe proteinuria (OR 3.5, 95% CI 1.9-6.5, P = 0.001), angina (OR 2.5, 95% CI 1.2-5.1, P = 0.008), anaemia (OR 2.9, 95% CI 1.7-4.9, P = 0.001), hyperuricemia (OR 2.4, 95% CI 1.4-4.1, P = 0.001), and metabolic acidosis (OR 2.0, 95% CI 1.2-3.1, P = 0.005). Other associations with advanced CKD were loss of spouse (widow/widower) (OR 3.2, 95% CI 1.4-7.4, P = 0.006), low transferrin (OR 2.4, 95% CI 1.1-5.1, P = 0.028), hyperkalemia (OR 5.4, 95% CI 1.2-24.1, P = 0.029), use of allopurinol (OR 2.4, 95% CI 1.4-4.3, P = 0.005) and doxazosin (OR 1.9, 95% CI 1.2-3.1, P = 0.006). Hypertension and diabetes mellitus were strongly associated with advanced CKD, suggesting a need for primary and secondary population-based prevention measures. Metabolic acidosis, anemia with low transferrin levels, hyperuricemia and hyperkalemia were highly prevalent in our patients, including those with early CKD, and they were strongly associated with advanced CKD, requiring clinicians and dietitians to be proactive in supporting the needs of CKD patients in meeting their daily dietary requirements towards preventing and slowing the progression of CKD.